POSHAN's abstract digest on maternal and child nutrition research - Issue 31 - Avula, Rasmi (International Food Policy Research Institute, 2019)
In this issue of Abstract Digest, we present to you a collection of articles on various outcomes, determinants and interventions related to maternal and child nutrition, from around the world and India, in particular. Additionally, we bring to you two salient reports, which have been released recently. UNICEF’s Children, Food and Nutrition: Growing well in a changing world highlights the state of the world’s children in 2019. India’s Comprehensive National Nutrition Survey provides significant information on malnutrition, anemia and micronutrient deficiencies among children and adolescents in India.